Exploring the relationship between residents’ perceived service quality and satisfaction on their current living place - Rahman, Muhammad Sabbir (Sryhwa Publication, 2014)
This research aim to examine the relationship between perceived service qualities and residents’ satisfaction when hygienic facilities play as a mediating role. A questionnaire-based survey was carried out with residents from the major residential areas of Dhaka city. This research applied four stages of statistical analyses such as descriptive analysis, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation modelling (SEM). The findings revealed that there is a strong relationship between services provided by the private companies towards resident’s satisfaction when hygienic facilities play as a mediating role